Sickness Absence and Sickness Presence Among Health and Care Employees in Sweden—Health Complaints, Health Behavior, and Future Long-Term Sickness Absence. Issue 6 (June 2021) - Helgesson, Magnus; Gustafsson, Klas; Marklund, Staffan; Aronsson, Gunnar; Leineweber, Constanze
Abstract : Objective: To describe if health complaints relate to health behavior in terms of sickness absence (SA) and sickness presence (SP) and to examine how complaints and health behavior predicts the risk for future long-term sickness absence (LTSA). Methods: Data originates from work environment surveys 2001 to 2013 and SA registers 2002 to 2016 of 1838 nurses, 7430 care assistants, and 40, 515 individuals in all other occupations. Descriptive and regression analyses were conducted. Results: Physical complaints and high SA in combination with high SP increased the risk of LTSA among nurses and care assistants. Nurses' high SP and care assistants' high SA elevated the LTSA risk. Conclusions: Strategies to reduce the reasons behind physical health complaints among health care workers are warranted. SP among nurses and SA among care assistants should be considered in the organization of their job demands.